Burden of illness of rheumatoid arthritis in Latin America: a regional perspective - Ramírez, L. A. (Clin Rheumatol, 2015)
Rheumatoid arthritis (RA) is one of the most important rheumatic diseases. Its prevalence varies among ethnic groups. Genetic and environmental factors influence its incidence and prevalence. This chronic disease will increase its frequency in the future due to population aging. The personal impact of this disease on many relevant areas of an individual requires special efforts to prevent and treat it properly. Adequate advice on several recently described risk factors such as tobacco and alcohol exposure, infections, obesity, and physical exercise should be part of every medical consultation. This knowledge should be incorporated to improve health care prevention programs. Patients and clinicians must work together through better communication skills to finally improve outcomes. Including RA in priority health care lists will need special effort from rheumatology societies and better communication with policy makers.